Embriologia e desenvolvimento de frutos e sementes de Eriocaulaceae e Cyperaceae (Poales) - Coan, Alessandra Ike [UNESP] (Universidade Estadual Paulista (Unesp), 2006)
The embryology and the seed development of Eriocaulaceae and Cyperaceae were studied here in order to contribute to the taxonomy and phylogeny of both families. The results given by different genera of Eriocaulaceae allowed us to strengthen the embryological uniformity of the family. The endothecial thickenings of the baseplate-type, the spiraperturate pollen grains, the antipodal cyst closely associated to the hypostase, and the operculated endotestal seeds are synapomorphies of Eriocaulaceae within Poales. The use of the character number of microsporangia of anthers in genera delimitation is not consistent, while those related to the seed coat seem to be more stable in establishing relationships between genera. The overall embryological features pointed out the necessity of a taxonomic revision in Eriocaulaceae, aiming at a more natural classification of its taxa. In Cyperaceae, the embryology and the fruit development were investigated in species of Hypolytrum and Rhynchospora, showing that most of these aspects are also uniform within the family. The endothecial thickenings of the spiral type, the Cyperaceous-type of simultaneous microsporogenesis, the trinucleate pollen grain of the pseudomonad type, the formation of a funicular obturator closely associated with the hypostase of the ovule, the Onagrad-Juncus variation embryogeny, and the fruit of the achene type with silica deposition clearly distinguish this family amongst the other Poales. Hypolytrum differs from Rhynchospora as well as from the other genera of Cyperaceae already studied for the spherical pseudomonads, with reticulate exine and central arrangement in the microsporangia, the micropyle formed by both the integuments, and the conspicuous parietal tissue which indicate its position as a basal group in the family. Moreover, the number and the ...(Complete abstract, click electronic address below).
Keywords: Anatomia vegetal; Monocotiledonea; Cyperaceous-type; Hypolytrum; Rhynchospora